1983
DOI: 10.1021/jo00168a022
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of oleandrose and the avermectin disaccharide, benzyl .alpha.-L-oleandrosyl-.alpha.-L-4-acetoxyoleandroside

Abstract: The synthesis of oleandrose, the key carbohydrate of the avermectins, and its elaboration to the avermectin disaccharide are described. The three contiguous asymmetric centers of oleandrose are introduced by the reaction of a -methoxyallyl boronate with (S)-2-(benzyloxy)propanol to give a 8.7:1.2:1.0 mixture of diastereomers, the major of which has the oleandrose stereochemistry. The disaccharide was prepared by coupling of l-S-(2-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(10 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…29 Several syntheses of oleandrose have been reported. 18,[30][31][32][33][34][35][36][37][38] We developed a new and practical chiral pool approach. Beginning with the commercial reagent 3,4-di-O-acetyl-6deoxy-L-glucal (8; Scheme 2), site-selective C4 deacetylation and benzylation was achieved under biphasic conditions (benzyl bromide, aqueous sodium hydroxide, dichloromethane).…”
Section: Resultsmentioning
confidence: 99%
“…29 Several syntheses of oleandrose have been reported. 18,[30][31][32][33][34][35][36][37][38] We developed a new and practical chiral pool approach. Beginning with the commercial reagent 3,4-di-O-acetyl-6deoxy-L-glucal (8; Scheme 2), site-selective C4 deacetylation and benzylation was achieved under biphasic conditions (benzyl bromide, aqueous sodium hydroxide, dichloromethane).…”
Section: Resultsmentioning
confidence: 99%
“…反之, 其 他羟基亲核试剂进攻脱氧糖异头位基团, 立体选择性恰 好相反(Scheme 4) [12] . 硫苷 [15] , Cu 2 + [16] , Ag + [17] , Hg 2+ [18] 或这些促进剂的组合 [19] ; 阳离子型促进 剂, 如: Br +[20] , I +[21] , Se + [10,22] , 烷基化试剂 [23] 等.…”
Section: -脱氧糖糖苷合成的方法unclassified
“…analysis with an authentic sample demonstrated that avermectin B 1 a monosaccharide was a minor metabolite; the major metabolite in all three samples, purified by preparative t.1.c. and h.p.l.c., was shown to be an equilibrium mixture of 8a-hydroxyavermectin Bla (53) and the corresponding ring-opened aldehyde (54), in an approximate ratio of 1 : 2.5. This structure was assigned by a…”
Section: Metabolismmentioning
confidence: 99%